BEAP: An End-User Agile Programming Paradigm for Business Applications - Shu, Cheng-Chun; Yu, Hai-Yan; Liu, Hao-Zhi (Journal of computer science and technology, 2006)
Business applications are subject to changes with technology trends or market demands. However, quick response to these changes is still a challenging issue. Most of the existing architectures (e.g., CORBA, Web Services) still expose the developers to excessive low-level details and force a tight coupling between program modules. For end users, developing, customizing, and reengineering applications remain difficult and time-consuming tasks. A high-level programming model is presented, together with a descriptive programming paradigm called BEAP, to facilitate end-user programming. In this approach, applications could be visually composed from well-defined software components called “funnels” in an event-driven fashion. Application examples have shown that, by raising the level of abstraction as well as simplifying the programming model, BEAP could empower end users to build business applications on demand with improved productivity.